2018
DOI: 10.1039/c7cc09809j
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor GLUT5-permeable fluorescent probes for fructose transport analysis

Abstract: The specificity of carbohydrate transporters towards their substrates poses a significant challenge for the development of molecular probes to monitor sugar uptake in cells for biochemical and biomedical applications. Herein we report a new set of coumarin-based fluorescent sugar conjugates applicable for the analysis of fructose uptake due to their free passage through the fructose-specific transporter GLUT5. The reported probes cover a broad range of the fluorescence spectrum providing essential tools for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…Fructose transporter photolabels, based on the 2,5-anhydro-D-mannitol core structure, interact well with GLUT5 [228]. Fluorescent GLUT5 probes based on the 2,5 anhydro-mannitol ring have also recently been designed [17,126]. The presence of a hydrogen bond donor at the C-3 position of 2,5-anhydro-D-mannitol derivatives is essential for effective binding to GLUT5 and fructose transport into tumour cells.…”
Section: Glut Specificity For Substrates and Inhibitorsmentioning
confidence: 99%
“…Fructose transporter photolabels, based on the 2,5-anhydro-D-mannitol core structure, interact well with GLUT5 [228]. Fluorescent GLUT5 probes based on the 2,5 anhydro-mannitol ring have also recently been designed [17,126]. The presence of a hydrogen bond donor at the C-3 position of 2,5-anhydro-D-mannitol derivatives is essential for effective binding to GLUT5 and fructose transport into tumour cells.…”
Section: Glut Specificity For Substrates and Inhibitorsmentioning
confidence: 99%
“…We have found that photoaffinity labelling compounds (FP1 and FP2, Figure 13e,f ), which are based on 2,5-anhydro- d -mannitol, combine well with GLUT5 when this is expressed in CHO cells [ 120 ], but so far, these analogues have not been extensively tested on GLUT5-expressing tissues. Fluorescent GLUT5 probes based on the 2,5-anhydro-mannitol ring have also recently been designed [ 121 ]. The potential for targeting the unique specificity of the fructose transporters is therefore good [ 108 , 116 ]; particularly now there are good crystal structures of GLUT5 [ 61 ].…”
Section: Looking To the Future Of Chemical Biology Approaches To Studmentioning
confidence: 99%
“…This suggest great promise for application of C-3 derived fructose conjugates in cellular uptake by GLUT5 as long as a spacer is taken with hydrogen bond donating capabilities. Finally, a new class of fluorescent probes based on C-6 coumarin substituted 2,5-AM conjugates was evaluated as application for the analysis of fructose uptake [132]. Electron withdrawing groups at the coumarin appeared to positively influence binding strength as uptake rates.…”
Section: Glut5 Affinity Based On Molecular Probesmentioning
confidence: 99%